Pengaruh Penambahan Puree Kecipir (Psophocarpus tetragonolobus L.) Terhadap Karakteristik Nugget Ikan Lele (Clarias gariepinus B.) - Putri, Putu Meta Pradnyani; Arihantana, Ni Made Indri Hapsari; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
This study was aimed to determine the effect addition of winged bean puree on the characteristics of catfish nugget and determine the best addition of winged bean puree to produce catfish nugget with the best characteristics. The experiment used is completely Randomized Design with addition of winged bean puree treatment consisting of 6 levels: 0%, 10%, 20%, 30%, 40%, and 50%. The treatment was repeated 3 times to obtain 18 experimental units. The data was analyzed by using analysis of variance and if the treatment had a significant effect, then followed by a Duncan Multiple Range Test (DMRT). The results showed that the addition of winged bean puree had a significant effect on water content, ash content, crude fiber content, color, aroma, taste, texture (hedonic), and color (intensities). Catfish nugget produced from the addition of 50% winged bean puree had the best characteristics, with 58,66% of water content, 1,58% of ash content, 16,58% of protein content, 4,54% of crude fiber content, the aroma was very liked and the color intensities was very green.